Religious-Sociocultural Networks and Social Capital Enhancement in Pesantren - Sutomo Sutomo; Aries Musnandar; Diaya Uddeen Deab Mahmoud Alzitawi; Sutrisno Sutrisno (Jurnal Pendidikan Islam, 2024)
Implementing society empowerment models is crucial for addressing micro-level problems where government services often fall short. Despite evidence that social capital significantly contributes to development and poverty reduction, there remains a gap in understanding specific strategies and outcomes of social capital-based empowerment initiatives. This study aims to fill this gap by investigating the unique learning concept of Pesantren Rakyat Sumberpucung (PRS), which emphasizes low- cost, independent, flexible, and mutual assistance principles. Utilizing framework which includes structural opportunity to meet, know-how of social interaction, sense of belonging, and ethos of mutuality, this study employed qualitative research design. Data were gathered through participant observation, semi-structured interviews with village-level stakeholders, in-depth interviews and focus group discussion. The results indicate that the integrative model known as "Pancarukun," which includes initiatives such as Jagong Mathon, Celengan, Ngaji Ngluruk, Lumbung Pesantren Rakyat, and Fatehahan, effectively strengthens socio-cultural-religious networks, fostering harmony and cooperation between PRS and the community. These strategies have successfully promoted a spirit of togetherness and consistent collaboration. In conclusion, PRS’s approach demonstrates the potential of integrative community-based strategies to address diverse problems across sectors such as economy, agriculture, education, and culture. By leveraging social capital, PRS has created a sustainable model of community empowerment that can serve as a blueprint for similar initiatives.